A new public key encryption scheme based on layered cellular automata - Zhang, Xing (2019)
Cellular automata (CA) based cryptosystem has been studied for almost three decades, yet most of previously reported researches focus on the symmetric key encryption schemes. Up to now, few CA based public key encryption scheme has been proposed. To fill the gap, in this paper, we propose a new public key encryption scheme based on layered cellular automata (LCA). Specifically, in the proposed scheme, based on the T-shaped neighborhood structure, we combine four one-dimensional reversible CAs (set as the private key) to form the transition rules of a two-dimension CA, where the two-dimension CA is set as the corresponding public key. Based on the hardness assumption of the Decisional Dependent CA problem in LCA, we formally prove the proposed scheme is indistinguishably secure against the chosen-plaintext attack (IND-CPA). In addition, we also use a numeric example to demonstrate its feasibility. Finally, analysis of key space and time efficiency are also carried out along with RSA-1024, and the simulation results demonstrate that our proposed scheme is more efficient.